BID Excellence Award recipient, Christysterra Johnny gains experience in Turkey - UMP, PNC (2019)
“Being a temporary English teacher in Altınküre Okullar, Sakarya, Turkey was the most meaningful experience of my life during my study in UMP,” said Christysterra Johnny, 23, graduated with a degree of Bachelor of Applied Science (Honours) Materials Technology. She received the Dimension BID Excellence Award at the 14th Universiti Malaysia Pahang (UMP) Convocation Ceremony.